Genetic evaluation of some newly developed soybean (Glycine max) genotypes in Benue State of Nigeria - Shaahu, A; Vange, T; Bello, L L (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during 2008–09 at Yandev in Benue state of Nigeria to evaluate 56 soybean (Glycine max L. Merrill) genotypes for genotypic and phenotypic variances, coefficient of variance, heritability, genetic advance for yield and its contributing traits. Significant variations among the genotypes, year and year × genotypes were observed for days to maturity, plant height, shattering, pods/plant, lodging. High heritability (broad sense) along with moderate genetic advance in per cent of mean was observed for shattering, days to 50% flowering and seed yield indicating that these characters would be best for phenotypic selection. The study indicated that there is appreciable variability with the genotypes under consideration for genetic advance. The genotypes TGx 1987-64F, TGx 1987-37F, TGx 1987-10F with relatively higher yield for two years are promising varieties for Yandev location.